Pu-erh Tea Water Extract Mediates Cell Cycle Arrest and Apoptosis in MDA-MB-231 Human Breast Cancer Cells - Xie, Jing; Yu, Haishuang; Song, Shuang; Fang, Chongye; Wang, Xuanjun; Bai, Zhongbin; Ma, Xiao; Hao, Shumei; Zhao, Hong-Ye; Sheng, Jun (Frontiers in Pharmacology, 2017)
Pu-erh tea is believed to have health benefits, the growth inhibition activity of Pu-erh tea on breast cancer cell has not been investigated. In this study, we examined the activity of Pu-erh tea water extract on apoptosis and cell cycle arrest in the human breast adenocarcinoma cell line MDA-MB-231 and clarified its underlying mechanism of action. We found that Pu-erh tea extract inhibited cell proliferation and induced apoptosis in a dose-dependent manner. We also found that Pu-erh tea extract inhibited tumor cell growth within 24 h via accumulation of cells in S phase. Further experiments showed that at 24 h, Pu-erh tea extract up-regulated the expressions of P-p53 (Ser15), p21 and P-JNK and down-regulated the expressions of PCNA, CyclinD1 and CyclinE at the protein level in MDA-MB-231 cells. In particular, the JNK-specific inhibitor SP600125 restored the induction of P-JNK, P-p53 (Ser15), p21, CyclinD1 and CyclinE by Pu-erh tea extract. Our results indicate that Pu-erh tea water extract inhibits cell proliferation of MDA-MB-231 cells through the induction of apoptosis and the stimulation of cell cycle arrest, which is mediated via activation of the JNK-related pathway.